EDUKASI PENERAPAN PROTOKOL KESEHATAN PENYELENGGARAAN KEGIATAN PADA MASA PANDEMI COVID 19 DI TPQ MASJID AWALULMU’MININ GAMPING - Deby Zulkarnain Rahadian Syah; Dewi Utari; Tetra Saktika Adinugraha (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2020)
The condition of the Covid 19 pandemic led to the limitation of the Al Qur'an learning process for the students. Starting from July 2020, the empowerment activities of TPQ Awalulmu'minin have been implemented with renewal activities three times, namely Monday, Tuesday, and Wednesday. Covid discussion activities just carried out handwashing, and at the beginning of the activity has been submitted for physical distance but because students are still in the category of children are also seen not according to the protocol contradiction Covid 19. The Covid 19 incident as of July 14, 2020, is positive and can be verified by 14 cases in the district Sleman, and 5 cases in the Gamping sub-district. The purpose of this activity is to familiarize students, teachers, and TPQ slicer in implementing the Health protocol. The method of implementation is health education for TPQ teachers, students, and administrators. Education counseling delivered with projector LCD slide media for 15 minutes. Then the discussion and question and answer were held. Continue to play through the five Health Insurance 19 protocols, namely students in good health, using face masks, cleaning hands, avoiding physical contact, and maintaining a minimum distance of 1 meter. After counseling during the three-day health protocol observations were observed. Santri denies that healthy and healthy life is coaxing Covid 19 by using the 5 step Health protocol. Santri and the teacher can wash their hands properly and correctly 100% protected health. Keywords: Learning the Al Qur'an during the Pandemic, Santri Health Protocol, Santri free Covid 19